Risky purchases – A study of consumers’ risk perceptions of plant-based leather alternatives - Darya Badiei Khorsand; Amy Benstead; Victoria Stephens; Janine Dixon; Gianpaolo Vignali; Daniella Ryding (Journal of Cleaner Production, 2026)

State of the UK Climate in 2025 - Mike Kendon; Amy Doherty; Dan Hollis; Emily Carlisle; Stephen Packman; Nick Rayner; Ségolène Berthou; Lucy Barker; Steve Turner; Jamie Hannaford; Svetlana Jevrejeva; Andrew Matthews; et al. (International Journal of Climatology, 2026)

Normative scores for the three factor eating questionnaire (TFEQ-R18) in a UK population-based cohort - Cara F. Ruggiero; Laura Kudlek; Julia Mueller; Simon J. Griffin; Stephen J. Sharp; Nick J. Wareham; Soren Brage; Nita G. Forouhi; Ken K. Ong; Amy Ahern (Appetite, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Multifrequency Electrical Impedance Myography Enhanced with Machine Learning for Screening Patients with Neuromuscular Disorders - Buket Sonbas-Cobb; Seward B. Rutkove; Baoguo Wei; Sara Robicheau; W. David Arnold; Kaneshia Hives; Amy Bartlett; Peter Riley; Aleah Pagan; Stephen M. Chrzanowski; Basil T. Darras; Stephen J. Kolb (Annals of Biomedical Engineering, 2026)
Purpose We evaluated surface electrical impedance myography (EIM) enhanced with machine learning to serve as a new office-based screening tool for neuromuscular disease Methods EIM of nine muscles was successfully performed in 119 adults and 111 children (approximately half healthy and half diseased) for a total of 3158 individual muscle measurements. Multifrequency data were processed with feature engineering and classification. Nested cross-validation assessed performance, with muscle-based predictions aggregated to participant via majority voting Results Single-feature analyses showed moderate-to-good discrimination (area-under-ROC curve of 0.62–0.73). When multifrequency features were used, participant-based logistic regression and extra trees ensemble models achieved 84% accuracy with 88.1% sensitivity in adults and 93% accuracy and 94.6% sensitivity in children. Beyond classification, regression using EIM predicted muscle strength with R 2 = 0.49, outperforming single-frequency correlations Conclusion These results demonstrate that machine learning-enhanced EIM can successfully distinguish individuals with neuromuscular disease from healthy individuals. Nevertheless, further studies in larger populations of people would help advance this technology to the point that it could serve as a convenient, office-based screening tool for neuromuscular disease.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

The collective application of shorebird tracking data to conservation - Autumn‐Lynn Harrison; Candace Stenzel; Alexandra Anderson; Jessica Howell; Richard B. Lanctot; Marley Aikens; Joaquín Aldabe; Liam A. Berigan; Joël Bêty; Erik Blomberg; Juliana Bosi de Almeida; Andy J. Boyce; et al. (Conservation Biology, 2026)
Addressing urgent conservation issues, such as the drastic declines of North American migratory birds, requires creative, evidence‐based, efficient, and collaborative approaches. The abundance of over 50% of monitored North American shorebird populations has declined by over 50% since 1980. To address these declines, we developed a partnership of scientists and practitioners called the Shorebird Science and Conservation Collective (hereafter the collective ). The collective was founded to translate the combined findings of shorebird tracking data into on‐the‐ground conservation action. With advice from an advisory group, the collective acts as an intermediary whereby dedicated staff collate and analyze data contributions from scientists to support knowledge requests from conservation practitioners. In its first three years, data contributions from 75 organizations include over 7.1 million shorebird observations forming movement paths of 3420 individuals representing 36 species tracked across the Americas and have informed 18 conservation projects spanning education, land and species management, land conservation, and policy requests. Others engaged in translational science from big data could consider similar knowledge‐sharing models that prioritize usable data products, foster collaborative engagement between science experts and practitioners, build focused communities around topics or taxonomic groups, and employ a proof‐of‐concept phase to develop scalable solutions while making progress toward long‐term funding to sustain impact. As the volume of scientific data continues to grow, intermediaries, such as the collective, can be vital liaisons to rapidly integrate and interpret research to support conservation action. Dedicated to the memory of Shiloh Schulte and his conservation achievements for shorebirds.

Rainfall and temperature influence effectiveness of on-site sanitation intervention against E. coli contamination in Bangladeshi households - Caitlin G. Niven; Mahfuza Islam; Anna Nguyen; Andrew Mertens; Amy J. Pickering; Laura H. Kwong; Mahfuja Alam; Debashis Sen; Sharmin Islam; Mahbubur Rahman; Leanne Unicomb; Alan E. Hubbard; et al. (International Journal of Hygiene and Environmental Health, 2026)

Examining the effect of neighborhood sanitation coverage on childhood diarrheal disease in rural Bangladesh - Hannah Van Wyk; Andrew F. Brouwer; Jesse Contreras; Mahbubur Rahman; Mahfuza Islam; Amy J. Pickering; Benjamin F. Arnold; Stephen P. Luby; John M. Colford; Matthew Freeman; Ayse Ercumen; Joseph N.S. Eisenberg (International Journal of Hygiene and Environmental Health, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Changes in Key Biodiversity Area networks following national comprehensive assessments - Andrew J. Plumptre; Zoltan Waliczky; Daniele Baisero; Olivia Crowe; Jeannot Kivono; Cecilia Tobar; Maria Gabriela Toscano; Natalia Boulad; Hugo Costa; Camila Davila; Sophie Dirou; Eleuterio Duarte; et al. (Conservation Biology, 2026)
Key Biodiversity Areas (KBAs) are sites of significance for the global persistence of biodiversity. Based on the Global Standard for the Identification of Key Biodiversity Areas (KBA Standard), published in 2016, sites are currently being assessed for KBA designation in a growing number of countries across the world. For these assessments, the KBA criteria are applied to all species and ecosystems with available data. We reviewed the first comprehensive assessments of 11 countries and compared the KBA network before and after assessments. The mean (SD) number of KBAs per country increased by 69.6% (102.1), and the mean total extent of KBAs per country increased by 164.2% (150.7). More than half of the KBAs in 2024 had >50% of their area outside the 2019 KBAs, indicating a substantial increase in KBA extent (54.0% [18.8] of KBAs). The mean proportion of each KBA covered by protected or conserved areas decreased from 56.2% (20.2) to 44.5% (15.5), owing to the incorporation of unprotected sites in the KBA network. On average, 41.1% (14.0) of sites in each country (mean 44.5 [46.4] sites per country) and 47.2% (20.5) of new KBA area after the assessment were completely unprotected, indicating that many of the new sites were not recognized in national protected area networks as significant for biodiversity before the assessment. Making a comprehensive assessment of KBAs increased the combined coverage of protected and conserved area networks from 25.4% (10.6) to 32.0% (13.1) in each country and thus contributed to reducing biodiversity loss. Therefore, comprehensive assessments of KBAs led to a substantially increased number and extent of recognized sites of importance for biodiversity published in the World Database of KBAs. Where such assessments have not been made, many important areas for biodiversity may be overlooked. We therefore encourage other nations to update their KBA networks to inform efforts to meet the goals and targets of the Kunming–Montreal Global Biodiversity Framework.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Correction: The Natural History Study and Biomarker Collection of the Clinical Research Consortium for the Study of Cerebellar Ataxia (CRC-SCA) - Yicheng Lin; Nadia Amokrane; Sandie Worley; Lauren R. Moore; Andrew Rosen; Laura P. Crespo; Kelsey Trace; Tetsuo Ashizawa; Andrew Billnitzer; Susan Perlman; Aaron Fisher; Khalaf Bushara; et al. (The Cerebellum, 2025)

Analysis of IgG responses to Sarcocystis neurona in horses with equine protozoal myeloencephalitis (EPM) suggests a Th1-biased immune response - Catherine J. Angwin; Izabela de Assis Rocha; Stephen M. Reed; Jennifer K. Morrow; Amy Graves; Daniel K. Howe (Veterinary Immunology and Immunopathology, 2025)

Microbial transformation and mineral adsorption control chemical evolution of soil organic matter during semi-arid ecosystem development - Hai-Ruo Mao; Stephen C. Hart; Derek Peak; Amy M. McKenna; Mengqiang Zhu (Geochimica et Cosmochimica Acta, 2025)

The Properties of Individual Fire Events Are Essential for Understanding Global Fire Regimes - Adam L. Mahood; Ty Tuff; Megan E. Cattau; Virginia Iglesias; Thomas E. Hanson; Jilmarie Stephens; Nayani Ilangakoon; Maxwell C. Cook; R. Chelsea Nagy; David Barnard; E. Natasha Stavros; Amy DeCastro; et al. (Global Ecology and Biogeography, 2025)
Aim As fire activity changes globally, we need to better understand the spatial and temporal characteristics of the individual events that, when aggregated, constitute fire regimes. Most global studies analyze point detections of burned area, without delineating or considering the properties of individual events. Furthermore, there is a critical need to understand fire patterns within the context of the geopolitical boundaries within which fires are managed. Location Global. Time Period 2003–2020. Major Taxa Studied Fire. Methods We divided 241 countries by Köppen‐Geiger climate classifications and quantified four event‐based fire regime metrics: size, duration, and mean and maximum growth rate; and four area‐based metrics: burned area, number of fires, season length, and season peak. We examined the correlations among fire regime components, and between each fire regime component and climate normals. We quantified temporal trends, and used mixed models to analyze how climate and landcover change were associated with event‐based components of fire regimes. Results Event‐based metrics were weakly correlated with area‐based metrics. Countries with warmer and less variable climates had high burned area, more fire events, longer season lengths and shorter event durations. Countries with high annual temperature range and low precipitation tended to have fewer events but larger fires that were faster‐spreading and occurred later in the year. The growth rate and size of individual fire events are increasing in 18% and 21% of regions we analysed, respectively. Interannual variability in size and growth rate was associated with aridity increases in boreal areas, and landcover changes in arid areas. Main Conclusions Drivers of burned area and fire seasonality are well understood but largely unrelated to the properties of individual events. A more detailed understanding of the spatial and temporal aspects of fire events at broad scales will assist fire management efforts in preparing for a warmer future.

Fossilisation of Fish Soft Tissue in Oxidative Microniches of Anoxic Sediments - Amy L. Elson; Lorenz Schwark; Paul F. Greenwood; Madison Tripp; Alex I. Holman; Michael E. Böttcher; Peter Hopper; Robert H. C. Madden; Luke M. Brosnan; Jessica H. Whiteside; Stephen F. Poropat; Lance Grande; et al. (Environmental Microbiology, 2025)
Organic analyses of past organisms enhance our understanding of Earth's evolutionary history, complementing the macrofossil record. Biomolecular remains are typically vulnerable to diagenetic mineralisation, but can persist in exceptional depositional settings such as Lagerstätten. Their preservation is usually linked to anoxic conditions that exclude aerobic degraders. However, we report intact skin tissue of the fossil fish Diplomystus dentatus from the Fossil Basin Lagerstätte (USA), preserved through phosphate permineralisation in an oxygen‐enriched microenvironment. Notably, only the skin with scales retained tissue integrity, and this organic material was closely associated with fluorapatite absent from the surrounding matrix. Geochemical analyses revealed higher oxidation states in the skin than in vertebrae and bones, likely due to early degradation of the fatty acid‐rich dermis. Redox‐sensitive biomarkers and isotopic data (δ 15 N) indicated a less reducing environment in the skin region compared to bones and the eye, yet more reducing than the surrounding sediment. This localised oxygen enrichment fostered sulphide‐oxidising bacteria, evidenced by mineral sulphates (barite) found only in the skin. Phosphatisation was likely driven by dermal breakdown and the release of H+, reducing alkalinity and enabling phosphate mineralisation over the carbonate system.

Associations between floor material and E. coli contamination in rural Bangladeshi households - Sumaiya Tazin; Mahfuza Islam; Amy J. Pickering; Laura H. Kwong; Andrew Mertens; Caitlin Niven; Benjamin F. Arnold; Alan E. Hubbard; Mahfuja Alam; Debashis Sen; Sharmin Islam; Mahbubur Rahman; et al. (International Journal of Hygiene and Environmental Health, 2025)

The Natural History Study and Biomarker Collection of the Clinical Research Consortium for the Study of Cerebellar Ataxia (CRC-SCA) - Yicheng Lin; Nadia Amokrane; Sandie Worley; Lauren R. Moore; Andrew Rosen; Laura P. Crespo; Kelsey Trace; Tetsuo Ashizawa; Andrew Billnitzer; Susan Perlman; Aaron Fisher; Khalaf Bushara; et al. (The Cerebellum, 2025)

Integration of computational models to predict botanical phytochemical constituent clearance routes by the Extended Clearance Classification System (ECCS) - Yitong Liu; Michael Lawless; Amy L. Roe; Stephen S. Ferguson (Toxicology and Applied Pharmacology, 2025)

Practical global sampling methods for estimating area and map accuracy of land cover and change - Alexandra Tyukavina; Stephen V. Stehman; Amy H. Pickens; Peter Potapov; Matthew C. Hansen (Remote Sensing of Environment, 2025)

State of the UK Climate in 2024 - Mike Kendon; Amy Doherty; Dan Hollis; Emily Carlisle; Stephen Packman; Svetlana Jevrejeva; Andrew Matthews; Joanne Williams; Judith Garforth; Tim Sparks (International Journal of Climatology, 2025)

Expression of corticoid‐regulatory genes in the gills of Atlantic salmon ( Salmo salar ) parr and smolt and during salinity acclimation - Makoto Kusakabe; Takashi Yada; Graham Young; Amy M. Regish; Stephen D. McCormick (Journal of Fish Biology, 2025)
In teleost fishes, cortisol is the major corticoid and has both glucocorticoid and mineralocorticoid actions. However, how fish tissues discriminate between these distinct corticosteroid actions is unclear. In mammals, the major factors responsible for intracellular corticosteroid regulation are glucocorticoid receptors ( gr s) and the mineralocorticoid receptor ( mr ), but their role in osmoregulation of fish is unclear. 11β‐hydroxysteroid dehydrogenases ( hsd11b s) control the levels of intracellular corticosteroids by converting from bioactive forms to inert forms. To investigate how Atlantic salmon ( Salmo salar ) respond to cortisol in different physiological or environmental conditions, we performed comparisons of parr and smolt, and osmotic challenge experiments to examine the physiological responses and gill transcript levels of genes underlying cortisol‐signalling, including gr1 , gr2 , mr , hsd11b2 and hsd11b3 . Because cortisol may interact with growth hormone and prolactin during salinity changes, transcript levels encoding growth hormone receptors ( ghr1 , ghr2 ) and the prolactin receptor ( prlr ) were also examined. Hsd11b2 transcript levels in seawater‐acclimated fish were consistently lower compared to fish acclimated to fresh water. After transfer to seawater, prlr transcript levels in fish significantly decreased and transcript levels of ghr1 , ghr2 and hsd11b3 showed no change or were slightly higher than those of freshwater control groups. Gr1 , gr2 and mr transcript levels were slightly but consistently higher in fish acclimated to fresh water relative to seawater. Our results indicate that changes in corticosteroid receptor and hsd11b2 transcript levels in the gills may be important mechanisms that regulate corticoid signals to achieve ion homeostasis in Atlantic salmon.

Socio-economic impacts and responses of the fishing industry and fishery managers to changes in small pelagic fish distribution and abundance - Felipe J. Quezada-Escalona; Desiree Tommasi; Isaac C. Kaplan; Pierre-Yves Hernvann; Timothy H. Frawley; Dorleta Garcia; Leire Ibaibarriaga; Sonia Sánchez-Maroño; Carryn de Moor; Jennifer Beckensteiner; Amy M. Schueller; Diana Feijó; et al. (Reviews in Fish Biology and Fisheries, 2025)
Small Pelagic Fish (SPF) exhibit large fluctuations in abundance and distribution in response to environmental variability. To maintain the resilience of fishing communities and develop effective and equitable climate adaptation strategies, improved understanding of how the fishing industry responds to spatio-temporal shifts within and across SPF populations is of critical importance. In this paper, we examine the responses of the fishing industry and resource managers to shifts in SPF availability worldwide and identify the resulting socioeconomic impacts. Leveraging SPF case studies from around the globe, we synthesize and compare the social-ecological linkages and feedbacks mediating how SPF fisheries respond to changes in marine ecosystem structure and function associated with (1) spatial shifts in species distribution and habitat availability, (2) ‘boom and bust’ population dynamics, or (3) changes in fish size and quality. Our case studies illustrate multiple paths towards the resilience of small pelagic fisheries and the fishing industry dependent upon them while emphasizing the need for increased coordination and cooperation across sectors and scales as climate change progresses. Drawing from the lessons offered by historical responses, as environmental variability increases, efforts to increase the flexibility and dynamism of SPF harvest portfolios and management strategies, licensing regimes, and international catch and allocation agreements may be required to ensure resource sustainability and human well-being.

The Cerebellar Neuropsychiatric Rating Scale in the Spinocerebellar Ataxias - Anna L. Burt; Maureen P. Daly; Janet C. Sherman; Jeremy D. Schmahmann; Susan L. Perlman; Liana S. Rosenthal; Sheng-Han Kuo; Tetsuo Ashizawa; Theresa Zesiewicz; Cameron Dietiker; Puneet Opal; Antoine Duquette; et al. (The Cerebellum, 2025)

Determinants of riverine migration success by Atlantic salmon ( Salmo salar ) smolts from rivers across the UK and Ireland - Jessica R. Rodger; Jemma Guthrie; Hannele M. Honkanen; Angus J. Lothian; Jessie Lilly; Marcus Walters; Richie Miller; Lorraine Hawkins; Al Reeve; Jamie Ribbens; Jim Henderson; Debbie Parke; et al. (Journal of Fish Biology, 2025)
There is some evidence that the river migration success of Atlantic salmon smolts, on their first migration to sea, varies both spatially and temporally. However, we have only a poor understanding of what may be driving this variation. In this study, we used acoustic telemetry to quantify the spatial and temporal variations in river migration success in Atlantic salmon smolts on their first migration to sea. In total 4120 Atlantic salmon smolts migrating through 22 rivers in Scotland, England, Ireland, and Northern Ireland over multiple years were included in the study. Individuals were defined as successful migrants if detected leaving the river to enter marine waters. The results show significant temporal (up to 4 years) and spatial (river) variations in migration success, with overall between‐river migration success varying from 3.4% to 97.0% and between years from 3.4% and 61.0%. Temporal variation in migration success was river specific, with some rivers being more temporally stable (exhibiting little variation between years) than others. Across all rivers and years, individual migration success was predicted positively by body condition and negatively by tag burden. The rate of migration success for a population (migration success standardized to a common river distance [proportion km −1 ]) was predicted by a number of environmental factors. The proportion of river catchment that comprised wetland and woodland positively predicted migration success, whereas the proportion of grassland and peatland in a catchment negatively predicted the rate of migration success. Although the mechanisms through which these effects may be operating were not directly examined in this study, we discuss some potential routes through which they may occur.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Insufficient space: Prioritizing large tree species and planting designs still fail to meet urban forest canopy targets - Paticia Rettondini Torquato; Christopher Szota; Amy K. Hahs; Stefan K. Arndt; Stephen J. Livesley (Landscape and Urban Planning, 2025)

Spatial Heterogeneity of Nitrogen Fixation and Denitrification in Streams - Erin K. Eberhard; Stephen M. Techtmann; Colden V. Baxter; Amy M. Marcarelli (Ecosystems, 2025)

Lake shape and the characteristics of migration behavior modify Atlantic salmon smolt migration success through lakes - Matthew Newton; Joseph McCallum; Hannele M. Honkanen; Alastair Stephen; Jessie M. Lilly; Danielle L. Orrell; Amy Green; Louise Chavarie; Jessica R. Rodger; Colin E. Adams (Journal of Fish Biology, 2025)
Migration is a high‐risk behavior. For the Atlantic salmon, Salmo salar , migrating from its river nursery area to marine feeding grounds, the magnitude of risk varies with habitat type. Passage through lakes, in particular, is associated with low rates of migration success. Downstream migrating salmon smolts are rheotactic when migrating in rivers, but lakes typically provide poorer directional currents for migrating salmon. In this study we tested if, in the absence of clear navigational cues in lakes, Atlantic salmon smolts switch to a random search strategy to find the outflowing river. We constructed random search simulations to test if lake basin shape has an effect on migration success. We also compared simulated migration characteristics with migrations of salmon smolts through five real lakes for which there are telemetry data for migrating salmon. Correlated random walk simulations showed that a random search strategy could be successful for all lake shapes tested but was more successful in curved (round and elliptical) than rectangular basin shapes. Rectangular basins with the migration start and stop points at the ends of the lake had a higher success than those where these points were perpendicular to the axis of the lake. In general, a random walk model predicted the migration success rate of fish tracked through real lakes. However, for two lakes the simulated migration success exceeded that of actual success, suggesting that fish passing through these lakes were not adopting a random search strategy. We speculate that this is the result of either conflicting navigational cues which inhibit smolts from finding the lake outlet or that they temporarily suspend migration (e.g., to feed). Modelling predicted that for small lakes, directional swimming in short steps (ca. 100 m) followed by turns with very low variation from the direction of travel resulted in the highest migration success. For larger lakes, longer step lengths but also with low turn variation (simulated turning angle drawn from distributions of standard deviation 2 ° and 5 ° around a mean of 0 ° ) resulted in the highest migration success. We conclude that navigation in downstream migrating salmon smolts switches from rheotaxis in rivers to a random search tactic in lakes except where residual flow cues in some lakes prevent this, at times resulting in suboptimal navigation outcomes.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Atmospheric Pressure Rivalry Between the Arctic and Northern Pacific: Implications for Alaskan Climate Variability - Igor V. Polyakov; Thomas J. Ballinger; James E. Overland; Stephen J. Vavrus; Seth L. Danielson; Rick Lader; Uma S. Bhatt; Amy S. Hendricks; Franz J. Mueter (International Journal of Climatology, 2024)
Located at the confluence of the Arctic and North Pacific and with Alaska at its heart, the Pacific Arctic Region (PAR) is a unique and interconnected regional climate system. Significant climatic changes in the PAR are described by a novel, mobile monthly Alaska Arctic Front (AAF) index, which is defined by sea level pressure differences between the migratory cores of the Beaufort High and Aleutian Low. Regional climate variability associated with the AAF shows prominent decadal signatures that are driven by the opposing effects of the North Pacific and the Arctic atmospheric pressure fields. Low AAF (negative phase) is dominated by North Pacific forcing, whereas high AAF (positive phase) is dominated by Arctic atmospheric processes. The recent (2011–2021) negative AAF phase, which is associated with the westward displacement of Aleutian Low explaining stronger northward winds and enhanced water transport northward through Bering Strait, is conducive to increased oceanic heat and freshwater content, reduced regional sea ice cover in the PAR, and to the expansion of Pacific species into the Arctic. These factors are all indicators of the Pacification of the Arctic Ocean, a key feature of climate change related to progression of anomalous Pacific water masses and biota into the polar basins. It is not yet clear if or when the recent phase of decadal variability will change and alter the rate of Pacification of the Arctic climate system.

Tetracycline and Oxacillin Act Synergistically on Biofilms and Display Increased Efficacy In Vivo Against Staphylococcus aureus - Amy K. Tooke; Rebecca E. Hodges; Josie F. Pyrah; Kenneth W. Bayles; Stephen A. Renshaw; Simon J. Foster (Current Microbiology, 2024)
Oxacillin (bactericidal) and tetracycline (bacteriostatic) are clinically relevant antibiotics that are routinely prescribed to treat Staphylococcus aureus infections but not conventionally used in combination. There is an urgent need for treatment regimens that can act upon biofilms during infection, associated with chronic infections on indwelling devices, as well as acute planktonic (systemic) infection. Here we show that in an in vitro model oxacillin and tetracycline act synergistically against S. aureus UAMS-1 biofilms, reducing the concentration of both antibiotics necessary to eradicate an established biofilm. Using an in vivo zebrafish larval infection model with S. aureus NewHG, they display improved bacterial clearance compared to each drug alone and can counteract a loss of host phagocytes, an important innate defence against S. aureus . In these cases, the bacteriostatic nature of tetracycline enhances rather than dampens the bactericidal action of oxacillin, although an exact mechanism remains to be elucidated. We suggest a dual therapy could be of clinical use against biofilm-forming S. aureus and has a potential use in patients with a compromised immune system.

Biogeographical Variation in Termite Distributions Alters Global Deadwood Decay - Stephanie J. Law; Habacuc Flores‐Moreno; Catherine L. Parr; Stephen Adu‐Bredu; Katherine Bunney; William K. Cornwell; Fidèle Evouna Ondo; Jeff R. Powell; Gabriel W. Quansah; Mark P. Robertson; Amy E. Zanne; Paul Eggleton (Global Ecology and Biogeography, 2024)
Aim Termites are a crucial group of macroinvertebrates regulating rates of deadwood decomposition across tropical and subtropical regions. When examining global patterns of deadwood decay, termites are treated as a homogenous group. There exist key biogeographical differences in termite distribution. One such clear distinction is the distribution of fungus‐growing termites (FGT, subfamily Macrotermitinae). Considering that climate will have shaped termite distribution and ecosystem processes, we evaluate the roles of termite distribution (presence of FGT) and climate (aridity) on global patterns in deadwood decay. Location Between 46° N‐43° S and 175° E‐85° W. Time Period Present (between 2016 and 2021). Major Taxa Studied Termites (Blattodea: Termitoidae). Methods We add salient data to an existing global dataset on deadwood decomposition, including new data from five existing sites and seven additional African sites. We analyse a dataset spanning six continents, 16 countries and 102 experimental sites. Firstly, we evaluate climatic differences (mean annual temperature, mean annual precipitation and mean annual aridity) between sites with and without FGT. Secondly, using aridity as a single comparative climate metric between sites that accounts for temperature and precipitation differences, we examine the interaction between FGT and aridity on global patterns of termite deadwood discovery and decay through multivariate logistic and linear regressions. Results Termite‐driven decay and wood discovery increased with aridity; however, responses differed between FGT and NFGT sites. Wood discovery increased with aridity in FGT sites only, suggesting a greater role of FGT to deadwood decay in arid environments. On average, both termite discovery and decay of deadwood were approximately four times greater in regions with FGT compared with regions without FGT. Main Conclusions Termite discovery and decay of deadwood is climate dependent, and higher decay may be through greater discovery of deadwood in FGT sites. Inclusion of biogeographical differences in termite distribution could potentially alter current and future global estimates of deadwood turnover.

Botanical-induced toxicity: Liver injury and botanical-drug interactions. A report on a society of Toxicology Annual Meeting symposium - Igor Koturbash; R. Philip Yeager; Constance A. Mitchell; Stephen Ferguson; Victor J. Navarro; Mary F. Paine; Amy L. Roe (Regulatory Toxicology and Pharmacology, 2024)

Melting of Totten Glacier, East Antarctica since the Last Glacial Maximum Revealed by Beryllium Isotope Ratios of Marine Sediment - Zihan Huang; Bethany C. Behrens; Yosuke Miyairi; Takahiro Aze; Stephen Obrochta; Takato Takemura; Reisuke Kondo; Alexandra Post; Leanne K. Armand; Philip O'Brien; Amy Leventer; Yusuke Yokoyama (Global and Planetary Change, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

A paleoenvironmental and ecological analysis of biomarkers from the Eocene Fossil Basin, Green River Formation, U.S.A. - Amy L. Elson; Lorenz Schwark; Jessica H. Whiteside; Peter Hopper; Stephen F. Poropat; Alex I. Holman; Kliti Grice (Organic Geochemistry, 2024)

The impact of behavioural weight management interventions on eating behaviour traits in adults with overweight or obesity: a systematic review and meta-analysis - Laura Kudlek; Patricia Eustacio Colombo; Amy Ahern; Struan Tait; Natasha Reid; Milindu Wickramarachchi; Aiswarya Lakshmi; Stephen J. Sharp; Marie Spreckley; Julia Mueller; Rebecca A. Jones (Appetite, 2024)

Genomic evaluation of mud sunfish in the atlantic slope drainage - Stephen Knott; Richard Raesly; Daniel Hocking; Jay Stauffer; Amy Welsh (Fisheries Research, 2024)

State of the UK Climate 2023 - Mike Kendon; Amy Doherty; Dan Hollis; Emily Carlisle; Stephen Packman; Mark McCarthy; Svetlana Jevrejeva; Andrew Matthews; Joanne Williams; Judith Garforth; Tim Sparks (International Journal of Climatology, 2024)

The National Wastewater Surveillance System (NWSS): From inception to widespread coverage, 2020–2022, United States - Carly Adams; Megan Bias; Rory M. Welsh; Jenna Webb; Heather Reese; Stephen Delgado; John Person; Rachel West; Soo Shin; Amy Kirby (Science of The Total Environment, 2024)

Spatially analysed expansion of individual street tree crowns enables species-specific crown expansion predictions in different rainfall zones - Patricia Rettondini Torquato; Amy K. Hahs; Christopher Szota; Stefan K. Arndt; Qian (Chayn) Sun; Joe Hurley; Stephen J. Livesley (Urban Forestry & Urban Greening, 2024)

Estimation of ammonia deposition to forest ecosystems in Scotland and Sri Lanka using wind-controlled NH3 enhancement experiments - Ajinkya G. Deshpande; Matthew R. Jones; Netty van Dijk; Neil J. Mullinger; Duncan Harvey; Robert Nicoll; Galina Toteva; Gothamie Weerakoon; Sarath Nissanka; Buddhika Weerakoon; Maude Grenier; Agata Iwanicka; et al. (Atmospheric Environment, 2024)

Population genomic structure of a widespread, urban‐dwelling mammal: The eastern grey squirrel ( Sciurus carolinensis ) - Nicole A. Fusco; Bradley J. Cosentino; James P. Gibbs; Maximilian L. Allen; Alexander J. Blumenfeld; George H. Boettner; Elizabeth J. Carlen; Merri Collins; Catherine Dennison; Devin DiGiacopo; André‐Philippe Drapeau Picard; Jonathan Edmonson; et al. (Molecular Ecology, 2024)
Urbanization is a persistent and widespread driver of global environmental change, potentially shaping evolutionary processes due to genetic drift and reduced gene flow in cities induced by habitat fragmentation and small population sizes. We tested this prediction for the eastern grey squirrel ( Sciurus carolinensis ), a common and conspicuous forest‐dwelling rodent, by obtaining 44K SNPs using reduced representation sequencing (ddRAD) for 403 individuals sampled across the species' native range in eastern North America. We observed moderate levels of genetic diversity, low levels of inbreeding, and only a modest signal of isolation‐by‐distance. Clustering and migration analyses show that estimated levels of migration and genetic connectivity were higher than expected across cities and forested areas, specifically within the eastern portion of the species' range dominated by urbanization, and genetic connectivity was less than expected within the western range where the landscape is fragmented by agriculture. Landscape genetic methods revealed greater gene flow among individual squirrels in forested regions, which likely provide abundant food and shelter for squirrels. Although gene flow appears to be higher in areas with more tree cover, only slight discontinuities in gene flow suggest eastern grey squirrels have maintained connected populations across urban areas in all but the most heavily fragmented agricultural landscapes. Our results suggest urbanization shapes biological evolution in wildlife species depending strongly on the composition and habitability of the landscape matrix surrounding urban areas.

Randomized controlled trial of propranolol on social communication and anxiety in children and young adults with autism spectrum disorder - David Q. Beversdorf; Bradley Ferguson; Samantha Hunter; Kathy Hirst; Bridget Lolli; Katherine R. Bellesheim; Amy U. Barton; Julie Muckerman; Nicole Takahashi; Kimberly Selders; Ryan Holem; Kristin Sohl; et al. (Psychopharmacology, 2024)

Anoxia begets anoxia: A positive feedback to the deoxygenation of temperate lakes - Abigail S. L. Lewis; Maximilian P. Lau; Stephen F. Jane; Kevin C. Rose; Yaron Be'eri‐Shlevin; Sarah H. Burnet; François Clayer; Heidrun Feuchtmayr; Hans‐Peter Grossart; Dexter W. Howard; Heather Mariash; Jordi Delgado Martin; et al. (Global Change Biology, 2024)
Declining oxygen concentrations in the deep waters of lakes worldwide pose a pressing environmental and societal challenge. Existing theory suggests that low deep‐water dissolved oxygen (DO) concentrations could trigger a positive feedback through which anoxia (i.e., very low DO) during a given summer begets increasingly severe occurrences of anoxia in following summers. Specifically, anoxic conditions can promote nutrient release from sediments, thereby stimulating phytoplankton growth, and subsequent phytoplankton decomposition can fuel heterotrophic respiration, resulting in increased spatial extent and duration of anoxia. However, while the individual relationships in this feedback are well established, to our knowledge, there has not been a systematic analysis within or across lakes that simultaneously demonstrates all of the mechanisms necessary to produce a positive feedback that reinforces anoxia. Here, we compiled data from 656 widespread temperate lakes and reservoirs to analyze the proposed anoxia begets anoxia feedback. Lakes in the dataset span a broad range of surface area (1–126,909 ha), maximum depth (6–370 m), and morphometry, with a median time‐series duration of 30 years at each lake. Using linear mixed models, we found support for each of the positive feedback relationships between anoxia, phosphorus concentrations, chlorophyll a concentrations, and oxygen demand across the 656‐lake dataset. Likewise, we found further support for these relationships by analyzing time‐series data from individual lakes. Our results indicate that the strength of these feedback relationships may vary with lake‐specific characteristics: For example, we found that surface phosphorus concentrations were more positively associated with chlorophyll a in high‐phosphorus lakes, and oxygen demand had a stronger influence on the extent of anoxia in deep lakes. Taken together, these results support the existence of a positive feedback that could magnify the effects of climate change and other anthropogenic pressures driving the development of anoxia in lakes around the world.

Genome-scale phylogeny and comparative genomics of the fungal order Sordariales - Noah Hensen; Lucas Bonometti; Ivar Westerberg; Ioana Onut Brännström; Sonia Guillou; Sandrine Cros-Aarteil; Sara Calhoun; Sajeet Haridas; Alan Kuo; Stephen Mondo; Jasmyn Pangilinan; Robert Riley; et al. (Molecular Phylogenetics and Evolution, 2023)

Land degradation neutrality: Testing the indicator in a temperate agricultural landscape - Amy Thomas; Laura Bentley; Chris Feeney; Stephen Lofts; Ciaran Robb; Ed C Rowe; Amanda Thomson; Eleanor Warren-Thomas; Bridget Emmett (Journal of Environmental Management, 2023)

Feasibility and acceptability of an acceptance-based guided self-help programme for weight loss maintenance - Julia Mueller; Rebecca A. Jones; Rebecca Richards; Jennifer Woolston; Fiona Whittle; Andrew J. Hill; Carly A. Hughes; Robbie Duschinsky; Stephen J. Sharp; Clare Boothby; Jennifer Bostock; Penny Breeze; et al. (Appetite, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

The influence of complex matrices on method performance in extracting and monitoring for microplastics - Leah M. Thornton Hampton; Hannah De Frond; Kristine Gesulga; Syd Kotar; Wenjian Lao; Cindy Matuch; Stephen B. Weisberg; Charles S. Wong; Susanne Brander; Silke Christansen; Cayla R. Cook; Fangni Du; et al. (Chemosphere, 2023)

Antibody Fc-binding profiles and ACE2 affinity to SARS-CoV-2 RBD variants - Ebene R. Haycroft; Samantha K. Davis; Pradhipa Ramanathan; Ester Lopez; Ruth A. Purcell; Li Lynn Tan; Phillip Pymm; Bruce D. Wines; P. Mark Hogarth; Adam K. Wheatley; Jennifer A. Juno; Samuel J. Redmond; et al. (Medical Microbiology and Immunology, 2023)
Emerging SARS-CoV-2 variants, notably Omicron, continue to remain a formidable challenge to worldwide public health. The SARS-CoV-2 receptor-binding domain (RBD) is a hotspot for mutations, reflecting its critical role at the ACE2 interface during viral entry. Here, we comprehensively investigated the impact of RBD mutations, including 5 variants of concern (VOC) or interest—including Omicron (BA.2)—and 33 common point mutations, both on IgG recognition and ACE2-binding inhibition, as well as FcγRIIa- and FcγRIIIa-binding antibodies, in plasma from two-dose BNT162b2-vaccine recipients and mild-COVID-19 convalescent subjects obtained during the first wave using a custom-designed bead-based 39-plex array. IgG-recognition and FcγR-binding antibodies were decreased against the RBD of Beta and Omicron, as well as point mutation G446S, found in several Omicron sub-variants as compared to wild type. Notably, while there was a profound decrease in ACE2 inhibition against Omicron, FcγR-binding antibodies were less affected, suggesting that Fc functional antibody responses may be better retained against the RBD of Omicron in comparison to neutralization. Furthermore, while measurement of RBD–ACE2-binding affinity via biolayer interferometry showed that all VOC RBDs have enhanced affinity to human ACE2, we demonstrate that human ACE2 polymorphisms, E35K (rs1348114695) has reduced affinity to VOCs, while K26R (rs4646116) and S19P (rs73635825) have increased binding kinetics to the RBD of VOCs, potentially affecting virus–host interaction and, thereby, host susceptibility. Collectively, our findings provide in-depth coverage of the impact of RBD mutations on key facets of host–virus interactions.

Neutralizing Antibody Validation Testing and Reporting Harmonization - Heather Myler; João Pedras-Vasconcelos; Todd Lester; Francesca Civoli; Weifeng Xu; Bonnie Wu; Inna Vainshtein; Linlin Luo; Mohamed Hassanein; Susana Liu; Swarna Suba Ramaswamy; Johanna Mora; et al. (The AAPS Journal, 2023)
Evolving immunogenicity assay performance expectations and a lack of harmonized neutralizing antibody validation testing and reporting tools have resulted in significant time spent by health authorities and sponsors on resolving filing queries. A team of experts within the American Association of Pharmaceutical Scientists’ Therapeutic Product Immunogenicity Community across industry and the Food and Drug Administration addressed challenges unique to cell-based and non-cell-based neutralizing antibody assays. Harmonization of validation expectations and data reporting will facilitate filings to health authorities and are described in this manuscript. This team provides validation testing and reporting strategies and tools for the following assessments: (1) format selection; (2) cut point; (3) assay acceptance criteria; (4) control precision; (5) sensitivity including positive control selection and performance tracking; (6) negative control selection; (7) selectivity/specificity including matrix interference, hemolysis, lipemia, bilirubin, concomitant medications, and structurally similar analytes; (8) drug tolerance; (9) target tolerance; (10) sample stability; and (11) assay robustness. Graphical Abstract

NH3 concentrations below the current critical level affect the epiphytic macrolichen communities – Evidence from a Northern European City - Sirkku Manninen; Kimmo Jääskeläinen; Amy Stephens; Agata Iwanicka; Sim Tang; Netty van Dijk (Science of The Total Environment, 2023)

Short-term ambient particulate matter pollution of different sizes and respiratory hospital admission in the Beibu Gulf area of Southern China - Haopeng Li; Lizhong Liang; Shiyu Zhang; Zhengmin (Min) Qian; Miao Cai; Xiaojie Wang; Stephen Edward McMillin; Amy E. Keith; Jing Wei; Yan Geng; Hualiang Lin (Atmospheric Environment, 2023)

Resource dilution in maternal feeding practices after birth of a secondborn - Cara F. Ruggiero; Amy M. Moore; Michele E. Marini; Stephen R. Kodish; Damon E. Jones; Susan M. McHale; Jennifer S. Savage (Appetite, 2023)

The influence of bait position on the catch of target and non-target sharks in a SMART drumline bather protection program - Rebecca S. Lipscombe; Anna Scott; Stephen Morris; Victor M. Peddemors; Amy F. Smoothey; Paul A. Butcher (Fisheries Research, 2023)

Individual North Atlantic right whales identified from space - Matus Hodul; Anders Knudby; Brigid McKenna; Amy James; Charles Mayo; Moira Brown; Delphine Durette‐Morin; Stephen Bird (Marine Mammal Science, 2023)
The population of the critically endangered North Atlantic right whale, Eubalaena glacialis , numbers approximately 336 individuals, and continues to decline. Current development and implementation of protection measures and monitoring of right whale presence relies on visual surveys from vessel and aerial platforms, and passive acoustic monitoring, which contribute to location data. Here we demonstrate that satellite imagery can be used to detect and confirm the North Atlantic right whales at a species level using newly available imaging methods, providing another tool to inform conservation efforts. Using optical satellite imagery with 15 cm resolution, 25 right whales were observed in Cape Cod Bay on April 24, 2021. Species confirmation was possible due to clearly visible callosity patterns indicative of their species within this range. Although the variations in callosity patterns commonly used to identify individuals were too small to be resolved at this image resolution, one whale with large distinctive markings visible on his body was identified at an individual level from satellite imagery alone. Although visual and acoustic survey methods can be combined for monitoring this species in critical habitats, satellite‐based monitoring can be especially helpful to understand whale presence outside the areas monitored with existing visual and acoustic detection methods.

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Microvascular anatomy suggests varying aerobic activity levels in the adipose tissues of diving tetrapods - Molly K. Gabler-Smith; Amy J. Berger; D. Mark Gay; Stephen T. Kinsey; Andrew J. Westgate; Heather N. Koopman (Journal of Comparative Physiology B, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Survival and spawning success of American shad (Alosa sapidissima) in varying temperatures and levels of glochidia infection - Shannon M. Bayse; Amy M. Regish; Stephen D. McCormick (Fish Physiology and Biochemistry, 2021)

Correction to: An evaluation of thermal imaging as a welfare monitoring tool for captive chimpanzees - Stephen R. Ross; Benjamin R. Lake; Amy Fultz; Lydia M. Hopper (Primates, 2021)

An evaluation of thermal imaging as a welfare monitoring tool for captive chimpanzees - Stephen R. Ross; Benjamin R. Lake; Amy Fultz; Lydia M. Hopper (Primates, 2021)

Systems analysis of miRNA biomarkers to inform drug safety - Amy L. Schofield; Joseph P. Brown; Jack Brown; Ania Wilczynska; Catherine Bell; Warren E. Glaab; Matthias Hackl; Lawrence Howell; Stephen Lee; James W. Dear; Mika Remes; Paul Reeves; et al. (Archives of Toxicology, 2021)
microRNAs (miRNAs or miRs) are short non-coding RNA molecules which have been shown to be dysregulated and released into the extracellular milieu as a result of many drug and non-drug-induced pathologies in different organ systems. Consequently, circulating miRs have been proposed as useful biomarkers of many disease states, including drug-induced tissue injury. miRs have shown potential to support or even replace the existing traditional biomarkers of drug-induced toxicity in terms of sensitivity and specificity, and there is some evidence for their improved diagnostic and prognostic value. However, several pre-analytical and analytical challenges, mainly associated with assay standardization, require solutions before circulating miRs can be successfully translated into the clinic. This review will consider the value and potential for the use of circulating miRs in drug-safety assessment and describe a systems approach to the analysis of the miRNAome in the discovery setting, as well as highlighting standardization issues that at this stage prevent their clinical use as biomarkers. Highlighting these challenges will hopefully drive future research into finding appropriate solutions, and eventually circulating miRs may be translated to the clinic where their undoubted biomarker potential can be used to benefit patients in rapid, easy to use, point-of-care test systems.

Montane Meadows: A Soil Carbon Sink or Source? - Cody C. Reed; Amy G. Merrill; W. Mark Drew; Beth Christman; Rachel A. Hutchinson; Levi Keszey; Melissa Odell; Sherman Swanson; Paul S. J. Verburg; Jim Wilcox; Stephen C. Hart; Benjamin W. Sullivan (Ecosystems, 2021)

Locally abundant, endangered Mariana swiftlets impact the abundance, behavior, and body condition of an invasive predator - Page E. Klug; Amy A. Yackel Adams; Shane R. Siers; Kevin M. Brindock; Stephen M. Mosher; M. J. Mazurek; William C. Pitt; Robert N. Reed (Oecologia, 2021)

Musclesense: a Trained, Artificial Neural Network for the Anatomical Segmentation of Lower Limb Magnetic Resonance Images in Neuromuscular Diseases - Baris Kanber; Jasper M Morrow; Uros Klickovic; Stephen Wastling; Sachit Shah; Pietro Fratta; Amy R McDowell; Matt G Hall; Chris A Clark; Francesco Muntoni; Mary M Reilly; Michael G Hanna; et al. (Neuroinformatics, 2021)

The Oncology and Sexuality, Intimacy, and Survivorship Program Model: An Integrated, Multi-disciplinary Model of Sexual Health Care within Oncology - Lauren M. Walker; Ericka Wiebe; Jill Turner; Amy Driga; Elisha Andrews-Lepine; Ashley Ayume; Joanne Stephen; Sarah Glaze; Reanne Booker; Corinne Doll; Tien Phan; Kerrie Brennan; et al. (Journal of Cancer Education, 2021)

Assessing the State of Coupled Social-Ecological Modeling in Support of Ecosystem Based Fisheries Management in the United States - Stephen Kasperski; Geret S. DePiper; Alan C. Haynie; Suzana Blake; Lisa L. Colburn; Amy Freitag; Michael Jepson; Mandy Karnauskas; Kirsten M. Leong; Douglas Lipton; Michelle Masi; Cameron Speir; et al. (Frontiers in Marine Science, 2021)
There has been a proliferation of coupled social-ecological systems (SES) models created and published in recent years. However, the degree of coupling between natural and social systems varies widely across the different coupled models and is often a function of the disciplinary background of the team conducting the research. This manuscript examines models developed for and used by NOAA Fisheries in support of Ecosystem Based Fisheries Management (EBFM) in the United States. It provides resource managers and interdisciplinary scientists insights on the strengths and weaknesses of the most commonly used SES models: end-to-end models, conceptual models, bioeconomic models, management strategy evaluations (MSEs), fisher behavior models, integrated social vulnerability models, and regional economic impact models. These model types are not unique to the literature, but allow us to differentiate between one-way coupled models – where outputs from one model are inputs into a second model of another discipline with no feedback to the first model, and two-way coupled models – where there are linkages between the natural and social system models. For a model to provide useful strategic or tactical advice, it should only be coupled to the degree necessary to understand the important dynamics/responses of the system and to create management-relevant performance metrics or potential risks from an (in)action. However, one key finding is to not wait to integrate! This paper highlights the importance of “when” the coupling happens, as timing affects the ability to fully address management questions and multi-sectoral usage conflicts that consider the full SES for EBFM or ecosystem based management (EBM) more generally.

Patterns and trends of fish mercury in New York State - Geoffrey Millard; Charles Driscoll; Mario Montesdeoca; Yang Yang; Mariah Taylor; Stephen Boucher; Amy Shaw; Wayne Richter; Eric Paul; Colleen Parker; Kiyoko Yokota (Ecotoxicology, 2020)

Landscape-scale drivers of fish faunal homogenization and differentiation in the eastern United States - Brandon K. Peoples; Amy J. S. Davis; Stephen R. Midway; Julian D. Olden; Lauren Stoczynski (Hydrobiologia, 2020)

Multiomic immune clockworks of pregnancy - Laura S. Peterson; Ina A. Stelzer; Amy S. Tsai; Mohammad S. Ghaemi; Xiaoyuan Han; Kazuo Ando; Virginia D. Winn; Nadine R. Martinez; Kevin Contrepois; Mira N. Moufarrej; Stephen Quake; David A. Relman; et al. (Seminars in Immunopathology, 2020)
Preterm birth is the leading cause of mortality in children under the age of five worldwide. Despite major efforts, we still lack the ability to accurately predict and effectively prevent preterm birth. While multiple factors contribute to preterm labor, dysregulations of immunological adaptations required for the maintenance of a healthy pregnancy is at its pathophysiological core. Consequently, a precise understanding of these chronologically paced immune adaptations and of the biological pacemakers that synchronize the pregnancy “immune clock” is a critical first step towards identifying deviations that are hallmarks of peterm birth. Here, we will review key elements of the fetal, placental, and maternal pacemakers that program the immune clock of pregnancy. We will then emphasize multiomic studies that enable a more integrated view of pregnancy-related immune adaptations. Such multiomic assessments can strengthen the biological plausibility of immunological findings and increase the power of biological signatures predictive of preterm birth

Macroscale drivers of Atlantic and Gulf Menhaden growth - Stephen R. Midway; Amy M. Schueller; Robert T. Leaf; Geneviève M. Nesslage; Raymond M. Mroch (Fisheries Oceanography, 2020)
The identification of anthropogenic and environmental drivers on length‐at‐age of fish stocks is important to understanding ecosystem dynamics and harvest intensity. We evaluated coastwide annual growth of n = 187,115 Atlantic Menhaden ( Brevoortia tyrannus ) and n = 299,185 Gulf Menhaden ( B. patronus ), using samples collected from the North, Mid‐, and South Atlantic from 1961 to 2016 and across the Gulf of Mexico from 1977 to 2016. Using hierarchical models of age 1 growth and age 2 growth, we evaluated a suite of candidate predictors including fishery landings, easterly (U) and northerly (V) wind velocity, river discharge, juvenile abundance, and the Atlantic Multi‐decadal Oscillation (AMO). We found age 2 growth rates were smaller than age 1 growth rates for both species and that Atlantic Menhaden growth rates were 3–4 times greater than Gulf Menhaden. Age 1 growth rate of Atlantic Menhaden was positively affected by landings lagged by one year, indicating a density‐dependent mechanism. In addition, AMO (negative effect), and wind U (positive effect) and wind V (negative effect) in the North Atlantic region were significant factors influencing coastwide age 1 Menhaden growth. Wind V (negative effect) and AMO (positive effect) influenced age 1 Gulf Menhaden growth. No environmental factors were found to have an effect on age 2 Atlantic Menhaden growth, and AMO was the only significant predictor (weak negative effect) of age 2 Gulf Menhaden growth. Fishing pressure was the primary influence on age 1 Atlantic Menhaden growth, whereas age 1 Gulf Menhaden growth was primarily influenced by environmental conditions.

Signaling from below: rodents select for deeper fruiting truffles with stronger volatile emissions - Ryan B. Stephens; Amy M. Trowbridge; Andrew P. Ouimette; W. Berk Knighton; Erik A. Hobbie; Paul C. Stoy; Rebecca J. Rowe (Ecology, 2020)
Many plant and fungal species use volatile organic compounds (VOCs) as chemical signals to convey information about the location or quality of their fruits or fruiting bodies to animal dispersers. Identifying the environmental factors and biotic interactions that shape fruit selection by animals is key to understanding the evolutionary processes that underpin chemical signaling. Using four Elaphomyces truffle species, we explored the role of fruiting depth, VOC emissions, and protein content in selection by five rodent species. We used stable isotope analysis of nitrogen (δ 15 N) in truffles to estimate fruiting depth, proton‐transfer‐reaction mass spectrometry to determine volatile emission composition, and nitrogen concentrations to calculate digestible protein of truffles. We coupled field surveys of truffle availability with truffle spore loads in rodent scat to determine selection by rodents. Despite presumably easier access to the shallow fruiting species, E. americanus (0.5‐cm depth) and E. verruculosus (2.5‐cm depth), most rodents selected for truffles fruiting deeper in the soil, E. macrosporus (4.1‐cm depth) and E. bartlettii (5.0‐cm depth). The deeper fruiting species had distinct VOC profiles and produced significantly higher quantities of odiferous compounds. Myodes gapperi (southern red‐backed vole), a fungal specialist, also selected for truffles with high levels of digestible protein, E. verruculosus and E. macrosporus . Our results highlight the importance of chemical signals in truffle selection by rodents and suggest that VOCs are under strong selective pressures relative to protein rewards. Strong chemical signals likely allow detection of truffles deep within the soil and reduce foraging effort by rodents. For rodents that depend on fungi as a major food source, protein content may also be important in selecting truffles.

Terrestrial Behavior in Titi Monkeys (Callicebus, Cheracebus, and Plecturocebus): Potential Correlates, Patterns, and Differences between Genera - João Pedro Souza-Alves; Italo Mourthe; Renato R. Hilário; Júlio César Bicca-Marques; Jennifer Rehg; Carla C. Gestich; Adriana C. Acero-Murcia; Patrice Adret; Rolando Aquino; Mélissa Berthet; Mark Bowler; Armando M. Calouro; et al. (International Journal of Primatology, 2019)

On the Future of Argo: A Global, Full-Depth, Multi-Disciplinary Array - Dean Roemmich; Matthew H. Alford; Hervé Claustre; Kenneth Johnson; Brian King; James Moum; Peter Oke; W. Brechner Owens; Sylvie Pouliquen; Sarah Purkey; Megan Scanderbeg; Toshio Suga; et al. (Frontiers in Marine Science, 2019)

Ocean Climate Observing Requirements in Support of Climate Research and Climate Information - Detlef Stammer; Annalisa Bracco; Krishna AchutaRao; Lisa Beal; Nathaniel L. Bindoff; Pascale Braconnot; Wenju Cai; Dake Chen; Matthew Collins; Gokhan Danabasoglu; Boris Dewitte; Riccardo Farneti; et al. (Frontiers in Marine Science, 2019)

Populus trichocarpa clade A PP2C protein phosphatases: their stress-induced expression patterns, interactions in core abscisic acid signaling, and potential for regulation of growth and development - Stephen B. Rigoulot; H. Earl Petzold; Sarah P. Williams; Amy M. Brunner; Eric P. Beers (Plant Molecular Biology, 2019)

Systematic Review and Meta-Analysis Toward Synthesis of Thresholds of Ocean Acidification Impacts on Calcifying Pteropods and Interactions With Warming - Nina Bednaršek; Richard Alan Feely; Ella L. Howes; Brian P. V. Hunt; Faycal Kessouri; Pablo León; Silke Lischka; Amy E. Maas; Karen McLaughlin; Nikolay P. Nezlin; Martha Sutula; Stephen B. Weisberg (Frontiers in Marine Science, 2019)

CAR T Cell Immunotherapy in Human and Veterinary Oncology: Changing the Odds Against Hematological Malignancies - Jonathan P. Mochel; Stephen C. Ekker; Chad M. Johannes; Albert E. Jergens; Karin Allenspach; Agnes Bourgois-Mochel; Michael Knouse; Sebastien Benzekry; Wesley Wierson; Amy K. LeBlanc; Saad S. Kenderian (The AAPS Journal, 2019)

The North Atlantic Aerosol and Marine Ecosystem Study (NAAMES): Science Motive and Mission Overview - Michael J. Behrenfeld; Richard H. Moore; Chris A. Hostetler; Jason Graff; Peter Gaube; Lynn M. Russell; Gao Chen; Scott C. Doney; Stephen Giovannoni; Hongyu Liu; Christopher Proctor; Luis M. Bolaños; et al. (Frontiers in Marine Science, 2019)

Volatile release, mobility, and mortality of diapausing Halyomorpha halys during simulated shipping movements and temperature changes - Laura J. Nixon; Amy Tabb; William R. Morrison; Kevin B. Rice; Eckehard G. Brockerhoff; Tracy C. Leskey; Chikako van Koten; Stephen Goldson; Michael Rostás (Journal of Pest Science, 2019)

Characterisation of the NRF2 transcriptional network and its response to chemical insult in primary human hepatocytes: implications for prediction of drug-induced liver injury - Ian M. Copple; Wouter den Hollander; Giulia Callegaro; Fiona E. Mutter; James L. Maggs; Amy L. Schofield; Lucille Rainbow; Yongxiang Fang; Jeffrey J. Sutherland; Ewa C. Ellis; Magnus Ingelman-Sundberg; Stephen W. Fenwick; et al. (Archives of Toxicology, 2019)

Separation, banking, and quality control of peripheral blood mononuclear cells from whole blood of melanoma patients - Martha Holland; Rachel Cunningham; Lake Seymour; Katja Kleinsteuber; Amy Cunningham; Tara Patel; Michael Manos; Ryan Brennick; Jun Zhou; F. Stephen Hodi; Mariano Severgnini (Cell and Tissue Banking, 2018)

Effects of ocean acidification on salinity tolerance and seawater growth of Atlantic salmon Salmo salar smolts - Stephen D. McCormick; Amy M. Regish (Journal of Fish Biology, 2018)
Human activity has resulted in increasing atmospheric carbon dioxide (CO 2 ), which will result in reduced pH and higher levels of CO 2 in the ocean, a process known as ocean acidification. Understanding the effects of ocean acidification (OA) on fishes will be important to predicting and mitigating its consequences. Anadromous species such as salmonids may be especially at risk because of their rapid movements between fresh water and seawater, which could minimize their ability to acclimate. In the present study, we examine the effect of future OA on the salinity tolerance and early seawater growth of Atlantic salmon Salmo salar smolts. Exposure to 610 and 1010 μatm CO 2 did not alter salinity tolerance but did result in slightly lower plasma chloride levels in smolts exposed to seawater compared with controls (390 μatm). Gill Na + –K + ‐ATPase activity, plasma cortisol, glucose and haematocrit after seawater exposure were not altered by elevated CO 2 . Growth rate in the first 2 weeks of seawater exposure was greater at 1010 μatm CO 2 than under control conditions. This study of the effects of OA on S. salar during the transition from fresh water to seawater indicates that elevated CO 2 is not likely to affect osmoregulation negatively and may improve early growth in seawater.

Effects of elevated temperature on osmoregulation and stress responses in Atlantic salmon Salmo salar smolts in fresh water and seawater - Luis Vargas‐Chacoff; Amy M. Regish; Andrew Weinstock; Stephen D. McCormick (Journal of Fish Biology, 2018)
Smolting in Atlantic salmon Salmo salar is a critical life‐history stage that is preparatory for downstream migration and entry to seawater that is regulated by abiotic variables including photoperiod and temperature. The present study was undertaken to determine the interaction of temperature and salinity on salinity tolerance, gill osmoregulatory proteins and cellular and endocrine stress in S. salar smolts. Fish were exposed to rapid changes in temperature (from 14 to 17, 20 and 24°C) in fresh water (FW) and seawater (SW), with and without prior acclimation and sampled after 2 and 8 days. Fish exposed simultaneously to SW and 24°C experienced 100% mortality, whereas no mortality occurred in any of the other groups. The highest temperature also resulted in poor ion regulation in SW with or without prior SW acclimation, whereas no substantial effect was observed in FW. Gill Na + –K + ‐ATPase (NKA) activity increased in SW fish compared to FW fish and decreased with high temperature in both FW and SW. Gill Nkaα1a abundance was high in FW and Nkaα1b and Na + –K + ‐2Cl‐ cotransporter high in SW, but all three were lower at the highest temperature. Gill Hsp70 levels were elevated in FW and SW at the highest temperature and increased with increasing temperature 2 days following direct transfer to SW. Plasma cortisol levels were elevated in SW at the highest temperature. Our results indicate that there is an important interaction of salinity and elevated temperature on osmoregulatory performance and the cellular stress response in S. salar , with an apparent threshold for osmoregulatory failure in SW above 20°C.

Racial differences in the relationship between tobacco, alcohol, and the risk of head and neck cancer: pooled analysis of US studies in the INHANCE Consortium - Kristin J. Voltzke; Yuan-Chin Amy Lee; Zuo-Feng Zhang; Jose P. Zevallos; Guo-Pei Yu; Deborah M. Winn; Thomas L. Vaughan; Erich M. Sturgis; Elaine Smith; Stephen M. Schwartz; Stimson Schantz; Joshua Muscat; et al. (Cancer Causes & Control, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Characterizing the Duration and Severity of Fishing Gear Entanglement on a North Atlantic Right Whale (Eubalaena glacialis) Using Stable Isotopes, Steroid and Thyroid Hormones in Baleen - Nadine S. J. Lysiak; Stephen J. Trumble; Amy R. Knowlton; Michael J. Moore (Frontiers in Marine Science, 2018)

The geographic distribution of seed-dispersal mutualisms in North America - Stephen B. Vander Wall; Sarah C. Barga; Amy E. Seaman (Evolutionary Ecology, 2017)

Contrasting effects of urban habitat complexity on metabolic functional diversity and composition of litter and soil bacterial communities - Alessandro Ossola; Cristina Aponte; Amy K. Hahs; Stephen J. Livesley (Urban Ecosystems, 2017)

Mechanistic evaluation of primary human hepatocyte culture using global proteomic analysis reveals a selective dedifferentiation profile - James A. Heslop; Cliff Rowe; Joanne Walsh; Rowena Sison-Young; Roz Jenkins; Laleh Kamalian; Richard Kia; David Hay; Robert P. Jones; Hassan Z. Malik; Stephen Fenwick; Amy E. Chadwick; et al. (Archives of Toxicology, 2017)

Multiple rare variants in high-risk pancreatic cancer-related genes may increase risk for pancreatic cancer in a subset of patients with and without germline CDKN2A mutations - Xiaohong R. Yang; Melissa Rotunno; Yanzi Xiao; Christian Ingvar; Hildur Helgadottir; Lorenza Pastorino; Remco van Doorn; Hunter Bennett; Cole Graham; Joshua N. Sampson; Michael Malasky; Aurelie Vogt; et al. (Human Genetics, 2016)

Habitat Complexity Enhances Comminution and Decomposition Processes in Urban Ecosystems - Alessandro Ossola; Amy K. Hahs; Michael A. Nash; Stephen J. Livesley (Ecosystems, 2016)

Increased percentages of regulatory T cells are associated with inflammatory and neuroendocrine responses to acute psychological stress and poorer health status in older men and women - Amy Ronaldson; Ahmad M. Gazali; Argita Zalli; Frank Kaiser; Stephen J. Thompson; Brian Henderson; Andrew Steptoe; Livia Carvalho (Psychopharmacology, 2016)

Epac2-deficiency leads to more severe retinal swelling, glial reactivity and oxidative stress in transient middle cerebral artery occlusion induced ischemic retinopathy - Jin Liu; Patrick Ka Kit Yeung; Lu Cheng; Amy Cheuk Yin Lo; Stephen Sum Man Chung; Sookja Kim Chung (Science China Life Sciences, 2015)

Climate remains an important driver of post‐European vegetation change in the eastern United States - Neil Pederson; Anthony W. D'Amato; James M. Dyer; David R. Foster; David Goldblum; Justin L. Hart; Amy E. Hessl; Louis R. Iverson; Stephen T. Jackson; Dario Martin‐Benito; Brian C. McCarthy; Ryan W. McEwan; et al. (Global Change Biology, 2015)

Effect of culture conditions on microRNA expression in primary adult control and COPD lung fibroblasts in vitro - Jun Ikari; Lynette M. Smith; Amy J. Nelson; Shunichiro Iwasawa; Yoko Gunji; Maha Farid; Xingqi Wang; Hesham Basma; Carol Feghali-Bostwick; Xiangde Liu; Dawn L. DeMeo; Stephen I. Rennard (In Vitro Cellular & Developmental Biology - Animal, 2015)

U-PB zircon tuff geochronology from the Karoo Basin, South Africa: implications of zircon recycling on stratigraphic age controls - Matthew P. McKay; Amy L. Weislogel; Andrea Fildani; Rufus L. Brunt; David M. Hodgson; Stephen S. Flint (International Geology Review, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Invasive Earthworms Deplete Key Soil Inorganic Nutrients (Ca, Mg, K, and P) in a Northern Hardwood Forest - Kit Resner; Kyungsoo Yoo; Stephen D. Sebestyen; Anthony Aufdenkampe; Cindy Hale; Amy Lyttle; Alex Blum (Ecosystems, 2015)

Impact of Exotic Earthworms on Organic Carbon Sorption on Mineral Surfaces and Soil Carbon Inventories in a Northern Hardwood Forest - Amy Lyttle; Kyungsoo Yoo; Cindy Hale; Anthony Aufdenkampe; Stephen D. Sebestyen; Kathryn Resner; Alex Blum (Ecosystems, 2015)

Seventy‐One Important Questions for the Conservation of Marine Biodiversity - E. C. M. PARSONS; BRETT FAVARO; A. ALONSO AGUIRRE; AMY L. BAUER; LOUISE K. BLIGHT; JOHN A. CIGLIANO; MELINDA A. COLEMAN; ISABELLE M. CÔTÉ; MEGAN DRAHEIM; STEPHEN FLETCHER; MELISSA M. FOLEY; REBECCA JEFFERSON; et al. (Conservation Biology, 2014)
The ocean provides food, economic activity, and cultural value for a large proportion of humanity. Our knowledge of marine ecosystems lags behind that of terrestrial ecosystems, limiting effective protection of marine resources. We describe the outcome of 2 workshops in 2011 and 2012 to establish a list of important questions, which, if answered, would substantially improve our ability to conserve and manage the world's marine resources. Participants included individuals from academia, government, and nongovernment organizations with broad experience across disciplines, marine ecosystems, and countries that vary in levels of development. Contributors from the fields of science, conservation, industry, and government submitted questions to our workshops, which we distilled into a list of priority research questions. Through this process, we identified 71 key questions. We grouped these into 8 subject categories, each pertaining to a broad component of marine conservation: fisheries, climate change, other anthropogenic threats, ecosystems, marine citizenship, policy, societal and cultural considerations, and scientific enterprise. Our questions address many issues that are specific to marine conservation, and will serve as a road map to funders and researchers to develop programs that can greatly benefit marine conservation. Setenta y Un Preguntas Importantes para la Conservación de la Biodiversidad Marina

Small Molecule Specific Run Acceptance, Specific Assay Operation, and Chromatographic Run Quality Assessment: Recommendation for Best Practices and Harmonization from the Global Bioanalysis Consortium Harmonization Teams - Eric J. Woolf; Stuart McDougall; Douglas M. Fast; Maristela Andraus; Matthew Barfield; Michael Blackburn; Ben Gordon; David Hoffman; Noriko Inoue; Gabriel Marcelin-Jimenez; Amy Flynn; Richard LeLacheur; et al. (The AAPS Journal, 2014)

Erratum to: A genome-wide association study of prostate cancer in West African men - Michael Blaise Cook; Zhaoming Wang; Edward D. Yeboah; Yao Tettey; Richard B. Biritwum; Andrew A. Adjei; Evelyn Tay; Ann Truelove; Shelley Niwa; Charles C. Chung; Annand P. Chokkalingam; Lisa W. Chu; et al. (Human Genetics, 2014)

A genome-wide association study of prostate cancer in West African men - Michael Blaise Cook; Zhaoming Wang; Edward D. Yeboah; Yao Tettey; Richard B. Biritwum; Andrew A. Adjei; Evelyn Tay; Ann Truelove; Shelley Niwa; Charles C. Chung; Annand P. Chokkalingam; Lisa W. Chu; et al. (Human Genetics, 2014)

Polymorphisms in genes related to one-carbon metabolism are not related to pancreatic cancer in PanScan and PanC4 - Max Leenders; Samsiddhi Bhattacharjee; Paolo Vineis; Victoria Stevens; H. Bas Bueno-de-Mesquita; Xiao-Ou Shu; Laufey Amundadottir; Myron Gross; Geoffrey S. Tobias; Jean Wactawski-Wende; Alan A. Arslan; Eric J. Duell; et al. (Cancer Causes & Control, 2013)

Diabetes and risk of pancreatic cancer: a pooled analysis from the pancreatic cancer cohort consortium - Joanne W. Elena; Emily Steplowski; Kai Yu; Patricia Hartge; Geoffrey S. Tobias; Michelle J. Brotzman; Stephen J. Chanock; Rachael Z. Stolzenberg-Solomon; Alan A. Arslan; H. Bas Bueno-de-Mesquita; Kathy Helzlsouer; Eric J. Jacobs; et al. (Cancer Causes & Control, 2013)

Role of Neurotrophins in the Development and Function of Neural Circuits That Regulate Energy Homeostasis - Samira Fargali; Masato Sadahiro; Cheng Jiang; Amy L. Frick; Tricia Indall; Valeria Cogliani; Jelle Welagen; Wei-Jye Lin; Stephen R. Salton (Journal of Molecular Neuroscience, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Characterization of 17 microsatellite loci for use in population genetic and mating system studies of the endangered North American passerine, loggerhead shrike (Lanius ludovicianus) - Angela Coxon; Amy A. Chabot; Stephen C. Lougheed; José Antonio Dávila; Bradley White (Conservation Genetics Resources, 2012)

The p38 mitogen-activated protein kinases modulate endothelial cell survival and tissue repair - Nobuhiro Kanaji; Amy Nelson; Diane S. Allen-Gipson; Tadashi Sato; Masanori Nakanishi; Xingqi Wang; YingJi Li; Hesham Basma; Joel Michalski; Maha Farid; Stephen I. Rennard; Xiangde Liu (Inflammation Research, 2012)

Fine mapping of 14q24.1 breast cancer susceptibility locus - Phoebe Lee; Yi-Ping Fu; Jonine D. Figueroa; Ludmila Prokunina-Olsson; Jesus Gonzalez-Bosquet; Peter Kraft; Zhaoming Wang; Kevin B. Jacobs; Meredith Yeager; Marie-Josèphe Horner; Susan E. Hankinson; Amy Hutchinson; et al. (Human Genetics, 2012)

Synergistic metabolism of a broad range of C1 compounds in the marine methylotrophic bacterium HTCC2181 - Kimberly H. Halsey; Amy E. Carter; Stephen J. Giovannoni (Environmental Microbiology, 2012)
Summary The 1.3 Mbp genome of HTCC2181, a member of the abundant OM43 clade of coastal bacterioplankton, suggested it is an obligate methylotroph. Preliminary experiments demonstrated that methanol and formaldehyde, but not other common C1 compounds such as methylamine, could support growth. Methanol concentrations in seawater are reportedly K s value of 19 µM. In contrast, no growth was observed in the presence of the methylated (C1) compounds, methyl chloride, trimethylamine‐oxide (TMAO) or dimethylsulfoniopropionate (DMSP) when they were the sole substrates. However, growth rate, maximum cell density and cellular ATP content were significantly enhanced when any of these methylated compounds were provided in the presence of a limiting concentration of methanol. These observations fit a model in which the metabolic intermediate formaldehyde is required for net carbon assimilation, allowing C1 substrates that do not produce a formaldehyde intermediate to be oxidized for energy, but not assimilated into biomass. Rates of methanol and TMAO oxidation and assimilation were measured with 14 C‐radiolabelled compounds in cultures of HTCC2181 and seawater microbial communities collected off the Oregon coast. The results indicated that in nature as well as in culture, C1 substrates are partitioned between those that are mainly oxidized to produce energy and those that are assimilated. These findings indicate that the combined fluxes of C1 compounds in coastal systems are sufficient to support significant populations of obligate methyltrophs by a metabolic strategy that involves the synergistic metabolism of multiple C1 compounds.

Non-receptor tyrosine kinase 2 reaches its lowest expression levels in human breast cancer during regional nodal metastasis - Qing-Xiang Amy Sang; Yan-Gao Man; You Me Sung; Zahraa I. Khamis; Lihua Zhang; Mi-Hye Lee; Stephen W. Byers; Ziad J. Sahab (Clinical & Experimental Metastasis, 2012)

Cervical Cancer Screening: Attitudes and Behaviors of Young Asian American Women - Grace J. Yoo; Mai Nhung Le; Stephen Vong; Regina Lagman; Amy G. Lam (Journal of Cancer Education, 2011)

Consulting Forestry / Certification and Ecosystem Services - James Coufal; Carl Wiedemann; Jacob Gorman; Larry Teeter; Yaoqi Zhang; Michael Kilgore; Kristell Miller; Stephanie Snyder; Sun Chang; Miriam Davis; Stanley Asah; J. Mark Fly; et al. (Journal of Forestry, 2011)
45The industrialization of the United States throughout the 19th century resulted in the exploitation of millions of acres of timberland across the country. Logging during that era was described by critics as “cut out and get out” because the land was usually abandoned after the merchantable timber was exhausted. Concern about future timber supplies and the effect of logging on watersheds spurred the development of professional forestry after the Civil War. The first forestry leaders, including Bernhard Fernow and Gifford Pinchot, encouraged private non-industrial forest owners to sustainably manage their woodlands and specifically warned against destructive logging practices—including “cutting the best and leaving the rest”—aka high-grading. During the 1920s and 30s both the Forest Service and SAF spurred initiatives to encourage sustainable timber harvesting practices on private forestland. Although great progress has been made in forest management, logging on most private non-industrial forest land in the east has not changed significantly since the 19th century. Landowners usually sell timber without using the services of a forester, allowing the buyer to selectively cut the most valuable trees in the woodlot. Although this can reduce future value by 70-90%, it remains common practice because both the landowner and the timber buyer maximize short term income. The timber value and productivity of millions of acres of woodland throughout the United States have been significantly degraded as a result. This paper will trace the history of high-grading as described by forestry leaders from the 19th century through the 21st and will show that much work remains unfinished.

Forest Policy / Biosecurity - Linda Heath; Clark Row; Robert Perschel; Douglas Boucher; Patricia Elias; Katherine Lininger; Calen May-Tobin; Earl Saxon; Steven Ruddell; Sally Collins; Sarah Ruddell; Mo Zhou; et al. (Journal of Forestry, 2011)
7Massive fires in Indonesian peatlands in the 1990s and in eastern Russian peatlands in 2002 and last year have highlighted the need to manage forests overlying peat deposits, as well as converted peat forests and open peatlands. Peat or peaty soils, contain 65% or more of partially decayed vegetation, can burn freely or underground. They cover some 10 percent of worldwide forests and contain 25 percent of all terrestrial carbon. Recent massive greenhouse gas (GHG) emissions from fires in forested peat and peatland in Indonesia and in Russia highlight the need for policies to reduce GHG emissions. We discuss major peatland areas and quantify their carbon stocks and potential GHG emissions. Trends show that year-to-year emissions are variable, with huge pulses that are a significant share of global GHG emissions. We group suggested policy options into three approaches. The first approach, which will reduce peat-related product demand, includes a) restricting peat, and products produced on cleared forested peatland, from being labeled or counted in GHG reduction achievements, as renewable (which palm oil currently is considered); b) developing full substitutes for horticultural peat (comprising about half mined peat use); and c) developing renewable power in countries still dependent on peat for power generation. These options reduce the rate of developing newly mined peat/forest areas. Options for a second approach, which treat already drained and cleared forested peatlands, are: d) restoring functioning peat ecosystems by closing drainage ditches, allowing natural rewetting, and “seeding” with peat vegetation fragments, e) requiring current peat operators to restore mined areas right after all peat is removed, and f) converting them to other land uses, despite the acidic conditions of mined peat bogs. These options sharply reduce risks of peat fires. Finally, a third group of policy options reduces ignition risks and limit fire spread: g) developing monitoring, suppression techniques, h) organizing local landowner protection groups and i) improving public fire organizations.

Fine mapping the KLK3 locus on chromosome 19q13.33 associated with prostate cancer susceptibility and PSA levels - Hemang Parikh; Zhaoming Wang; Kerry A. Pettigrew; Jinping Jia; Sarah Daugherty; Meredith Yeager; Kevin B. Jacobs; Amy Hutchinson; Laura Burdett; Michael Cullen; Liqun Qi; Joseph Boland; et al. (Human Genetics, 2011)

Differentiation of embryonic stem cells into fibroblast-like cells in three-dimensional type I collagen gel cultures - Shinsaku Togo; Tadashi Sato; Hisatoshi Sugiura; Xingqi Wang; Hesham Basma; Amy Nelson; Xiangde Liu; Tom W. Bargar; John G. Sharp; Stephen I. Rennard (In Vitro Cellular & Developmental Biology - Animal, 2011)

Functional traits and the growth–mortality trade‐off in tropical trees - S. Joseph Wright; Kaoru Kitajima; Nathan J. B. Kraft; Peter B. Reich; Ian J. Wright; Daniel E. Bunker; Richard Condit; James W. Dalling; Stuart J. Davies; Sandra Díaz; Bettina M. J. Engelbrecht; Kyle E. Harms; et al. (Ecology, 2010)
A trade‐off between growth and mortality rates characterizes tree species in closed canopy forests. This trade‐off is maintained by inherent differences among species and spatial variation in light availability caused by canopy‐opening disturbances. We evaluated conditions under which the trade‐off is expressed and relationships with four key functional traits for 103 tree species from Barro Colorado Island, Panama. The trade‐off is strongest for saplings for growth rates of the fastest growing individuals and mortality rates of the slowest growing individuals ( r 2 = 0.69), intermediate for saplings for average growth rates and overall mortality rates ( r 2 = 0.46), and much weaker for large trees ( r 2 ≤ 0.10). This parallels likely levels of spatial variation in light availability, which is greatest for fast‐ vs. slow‐growing saplings and least for large trees with foliage in the forest canopy. Inherent attributes of species contributing to the trade‐off include abilities to disperse, acquire resources, grow rapidly, and tolerate shade and other stresses. There is growing interest in the possibility that functional traits might provide insight into such ecological differences and a growing consensus that seed mass (SM), leaf mass per area (LMA), wood density (WD), and maximum height ( H max ) are key traits among forest trees. Seed mass, LMA, WD, and H max are predicted to be small for light‐demanding species with rapid growth and mortality and large for shade‐tolerant species with slow growth and mortality. Six of these trait–demographic rate predictions were realized for saplings; however, with the exception of WD, the relationships were weak ( r 2 r 2 80% of the explained variation and, after WD was included, LMA and H max made insignificant contributions. Virtually the full range of values of SM, LMA, and H max occurred at all positions on the growth–mortality trade‐off. Although WD provides a promising start, a successful trait‐based ecology of tropical forest trees will require consideration of additional traits.

Alteration in protein expression in estrogen receptor alpha-negative human breast cancer tissues indicates a malignant and metastatic phenotype - Ziad J. Sahab; Yan-Gao Man; Suzan M. Semaan; Robert G. Newcomer; Stephen W. Byers; Qing-Xiang Amy Sang (Clinical & Experimental Metastasis, 2010)

Alcohol intake and pancreatic cancer: a pooled analysis from the pancreatic cancer cohort consortium (PanScan) - Dominique S. Michaud; Alina Vrieling; Li Jiao; Julie B. Mendelsohn; Emily Steplowski; Shannon M. Lynch; Jean Wactawski-Wende; Alan A. Arslan; H. Bas Bueno-de-Mesquita; Charles S. Fuchs; Myron Gross; Kathy Helzlsouer; et al. (Cancer Causes & Control, 2010)

A comprehensive resequence analysis of the KLK15–KLK3–KLK2 locus on chromosome 19q13.33 - Hemang Parikh; Zuoming Deng; Meredith Yeager; Joseph Boland; Casey Matthews; Jinping Jia; Irene Collins; Ariel White; Laura Burdett; Amy Hutchinson; Liqun Qi; Jennifer A. Bacior; et al. (Human Genetics, 2010)

Variation in RTN3 and PPIL2 Genes Does not Influence Platelet Membrane β-Secretase Activity or Susceptibility to Alzheimer’s Disease in the Northern Irish Population - Robyn Carson; Amy Jayne McKnight; Stephen Todd; Wei Wei Liu; Shirley Heggarty; David Craig; Bernadette McGuinness; G. Brent Irvine; A. Peter Passmore; Janet A. Johnston (NeuroMolecular Medicine, 2009)

Comprehensive resequence analysis of a 97 kb region of chromosome 10q11.2 containing the MSMB gene associated with prostate cancer - Meredith Yeager; Zuoming Deng; Joseph Boland; Casey Matthews; Jennifer Bacior; Victor Lonsberry; Amy Hutchinson; Laura A. Burdett; Liqun Qi; Kevin B. Jacobs; Jesus Gonzalez-Bosquet; Sonja I. Berndt; et al. (Human Genetics, 2009)

Epitope-positive truncating MLH1 mutation and loss of PMS2: implications for IHC-directed genetic testing for lynch syndrome - Israel Zighelboim; Matthew A. Powell; Sheri A. Babb; Alison J. Whelan; Amy P. Schmidt; Mark Clendenning; Leigha Senter; Stephen N. Thibodeau; Albert de la Chapelle; Paul J. Goodfellow (Familial Cancer, 2009)

Elasticity analysis in epidemiology: an application to tick‐borne infections - Amy Matser; Nienke Hartemink; Hans Heesterbeek; Alison Galvani; Stephen Davis (Ecology Letters, 2009)
Ecology Letters (2009) 12: 1298–1305 Abstract The application of projection matrices in population biology to plant and animal populations has a parallel in infectious disease ecology when next‐generation matrices (NGMs) are used to characterize growth in numbers of infected hosts ( R 0 ). The NGM is appropriate for multi‐host pathogens, where each matrix element represents the number of cases of one type of host arising from a single infected individual of another type. For projection matrices, calculations of the sensitivity and elasticity of the population growth rate to changes in the matrix elements has generated insight into plant and animal populations. These same perturbation analyses can be used for infectious disease systems. To illustrate this in detail we parameterized an NGM for seven tick‐borne zoonoses and compared them in terms of the contributions to R 0 from three different routes of transmission between ticks, and between ticks and vertebrate hosts. The definition of host type may be the species of the host or the route of infection, or, as was the case for the set of tick‐borne pathogens, a combination of species and the life stage at infection. This freedom means that there is a broad range of disease systems and questions for which the methodology is appropriate.

Testing causal structure in the biogeography of avian extinctions on oceanic islands - Tim J. Karels; F. Stephen Dobson; Heather S. Zimbler‐DeLorenzo; Amy L. Skibiel (Journal of Biogeography, 2009)
In their recent comment in this journal, T. M. Blackburn and colleagues called into question the use of standardized partial regression modelling (also called path analysis and structural equation modelling) when null expectations for regression coefficients are not zero. Here, we answer their critique by showing how randomization can be used to illuminate and interpret causal modelling in analyses that have non‐zero expectations. Causal modelling is a powerful tool that can yield novel insights in biogeography when properly interpreted.

Phosphorus sources and demand during summer in a eutrophic lake - Amy M. Kamarainen; Rachel M. Penczykowski; Matthew C. Van de Bogert; Paul C. Hanson; Stephen R. Carpenter (Aquatic Sciences, 2009)

Nitrate removal in stream ecosystems measured by 15N addition experiments: Total uptake - Robert O. Hall; Jennifer L. Tank; Daniel J. Sobota; Patrick J. Mulholland; Jonathan M. O'Brien; Walter K. Dodds; Jackson R. Webster; H. Maurice Valett; Geoffrey C. Poole; Bruce J. Peterson; Judy L. Meyer; William H. McDowell; et al. (Limnology and Oceanography, 2009)
We measured uptake length of 15 NO 3 − in 72 streams in eight regions across the United States and Puerto Rico to develop quantitative predictive models on controls of NO 3 − uptake length. As part of the Lotic Intersite Nitrogen eXperiment II project, we chose nine streams in each region corresponding to natural (reference), suburban‐urban, and agricultural land uses. Study streams spanned a range of human land use to maximize variation in NO 3 − concentration, geomorphology, and metabolism. We tested a causal model predicting controls on NO 3 − uptake length using structural equation modeling. The model included concomitant measurements of ecosystem metabolism, hydraulic parameters, and nitrogen concentration. We compared this structural equation model to multiple regression models which included additional biotic, catchment, and riparian variables. The structural equation model explained 79% of the variation in log uptake length ( S Wtot ). Uptake length increased with specific discharge ( Q/w ) and increasing NO 3 − concentrations, showing a loss in removal efficiency in streams with high NO 3 − concentration. Uptake lengths shortened with increasing gross primary production, suggesting autotrophic assimilation dominated NO 3 − removal. The fraction of catchment area as agriculture and suburban‐urban land use weakly predicted NO 3 − uptake in bivariate regression, and did improve prediction in a set of multiple regression models. Adding land use to the structural equation model showed that land use indirectly affected NO 3 − uptake lengths via directly increasing both gross primary production and NO 3 − concentration. Gross primary production shortened S Wtot , while increasing NO 3 − lengthened S Wtot resulting in no net effect of land use on NO 3 − removal.

Nitrate removal in stream ecosystems measured by 15N addition experiments: Denitrification - Patrick J. Mulholland; Robert O. Hall; Daniel J. Sobota; Walter K. Dodds; Stuart E. G. Findlay; Nancy B. Grimm; Stephen K. Hamilton; William H. McDowell; Jonathan M. O'Brien; Jennifer L. Tank; Linda R. Ashkenas; Lee W. Cooper; et al. (Limnology and Oceanography, 2009)
We measured denitrification rates using a field 15 NO 3 − tracer‐addition approach in a large, cross‐site study of nitrate uptake in reference, agricultural, and suburban‐urban streams. We measured denitrification rates in 49 of 72 streams studied. Uptake length due to denitrification ( S Wden n) ranged from 89 m to 184 km (median of 9050 m) and there were no significant differences among regions or land‐use categories, likely because of the wide range of conditions within each region and land use. N 2 production rates far exceeded N 2 O production rates in all streams. The fraction of total NO 3 − removal from water due to denitrification ranged from 0.5% to 100% among streams (median of 16%), and was related to NH 4 + concentration and ecosystem respiration rate (ER). Multivariate approaches showed that the most important factors controlling S Wden were specific discharge (discharge / width) and NO 3 − concentration (positive effects), and ER and transient storage zones (negative effects). The relationship between areal denitrification rate ( U den ) and NO 3 − concentration indicated a partial saturation effect. A power function with an exponent of 0.5 described this relationship better than a Michaelis‐Menten equation. Although U den increased with increasing NO 3 − concentration, the efficiency of NO 3 − removal from water via denitrification declined, resulting in a smaller proportion of streamwater NO 3 − load removed over a given length of stream. Regional differences in stream denitrification rates were small relative to the proximate factors of NO 3 − concentration and ecosystem respiration rate, and land use was an important but indirect control on denitrification in streams, primarily via its effect on NO 3 − concentration.

The discriminative stimulus effects of dopamine D2- and D3-preferring agonists in rats - Mikhail N. Koffarnus; Benjamin Greedy; Stephen M. Husbands; Peter Grundt; Amy Hauck Newman; James H. Woods (Psychopharmacology, 2009)

Is (−)-Catechin a Novel Weapon of Spotted Knapweed (Centaurea stoebe)? - Stephen O. Duke; Amy C. Blair; Franck E. Dayan; Robert D. Johnson; Kumudini M. Meepagala; Daniel Cook; Joanna Bajsa (Journal of Chemical Ecology, 2009)

A six-year study of fire-related flowering cues and coexistence of two perennial grasses in a wet longleaf pine (Pinus palustris) savanna - J. Stephen Brewer; Amy L. Cunningham; Timothy P. Moore; Randell M. Brooks; Joanne L. Waldrup (Plant Ecology, 2009)

NO3 −-Driven SO4 2− Production in Freshwater Ecosystems: Implications for N and S Cycling - Amy J. Burgin; Stephen K. Hamilton (Ecosystems, 2008)

ORIGINAL ARTICLE: The biogeography of avian extinctions on oceanic islands - Tim J. Karels; F. Stephen Dobson; Heather S. Trevino; Amy L. Skibiel (Journal of Biogeography, 2008)
Aim To test the influences of island area, island isolation, and human‐introduced mammalian predators on avian extinctions that have occurred on oceanic islands worldwide. Location The oceanic islands of the world. Methods We augmented and re‐examined an existing data set for 218 oceanic islands by means of causal modelling using path analysis (a form of structural equation modelling) and a null model. Results The number of extinctions was not a simple function of the number of bird species on the various islands. Whereas introduced mammalian predators had an influence on the number of extinctions, island area (via indirect influences) and isolation (via direct influences) were equally or more important. Main conclusions The multiple influences of physical and biotic factors on past extinctions can be revealed through modelling the causal influences of physical attributes of islands on biological characteristics, and the causal influences of both physical and biological characteristics on extinctions.

Importance of Causal Analysis of Threats to Oceanic Avifaunas: Reply to Blackburn et al. - HEATHER S. TREVINO; AMY L. SKIBIEL; TIM J. KARELS; F. STEPHEN DOBSON (Conservation Biology, 2008)

Yawning and hypothermia in rats: effects of dopamine D3 and D2 agonists and antagonists - Gregory T. Collins; Amy Hauck Newman; Peter Grundt; Kenner C. Rice; Stephen M. Husbands; Cédric Chauvignac; Jianyong Chen; Shaomeng Wang; James H. Woods (Psychopharmacology, 2007)

Genetic variation in tumor necrosis factor and lymphotoxin-alpha (TNF–LTA) and breast cancer risk - Mia M. Gaudet; Kathleen M. Egan; Jolanta Lissowska; Polly A. Newcomb; Louise A. Brinton; Linda Titus-Ernstoff; Meredith Yeager; Stephen Chanock; Robert Welch; Beata Peplonska; Amy Trentham-Dietz; Montserrat Garcia-Closas (Human Genetics, 2007)

Genetic containment of forest plantations - Amy M. Brunner; Jingyi Li; Stephen P. DiFazio; Olga Shevchenko; Brooke E. Montgomery; Rozi Mohamed; Hao Wei; Cathleen Ma; Ani Anna Elias; Katherine VanWormer; Steven H. Strauss (Tree Genetics & Genomes, 2007)

Threats to Avifauna on Oceanic Islands - HEATHER S. TREVINO; AMY L. SKIBIEL; TIM J. KARELS; F. STEPHEN DOBSON (Conservation Biology, 2007)
Results of the study by of avifauna on oceanic islands suggest that distance from the mainland and time since European colonization have major influences on species extinctions and that island area is a significant but secondary contributing factor. After augmenting the data of the study on geographical properties for some of the islands they examined, we used a causal analysis approach with structural equation modeling to reexamine their conclusions. In our model geographical properties of islands, such as island area and isolation, were considered constraints on biological factors, such as the number of introduced mammalian predators and existing number of avifauna, that can directly or indirectly influence extinction. Of the variables we tested, island area had the greatest total influence on the threat of extinction due to its direct and indirect effects on the size of island avifauna. Larger islands had both a greater number of threatened bird species and more avifauna, increasing the number of species that could become threatened with extinction. Island isolation also had a significant, positive, and direct effect on threats to island avifauna because islands farther from the mainland had fewer current extant avifauna. Time since European colonization had a significant negative, but relatively weaker, influence on threats compared with the traditional biogeographic factors of island area and distance to the mainland. We also tested the hypothesis that the amount of threat is proportionally lower on islands that have had more extinctions (i.e., there is a “filter effect”). Because the proportion of bird extinctions potentially explained only 2.3% of the variation in the proportion of threatened species on islands, our results did not support this hypothesis. Causal modeling provided a powerful tool for examining threat of extinction patterns of known and hypothesized pathways of influence.

Genetic alterations in caspase-10 may be causative or protective in autoimmune lymphoproliferative syndrome - Shigui Zhu; Amy P. Hsu; Marla M. Vacek; Lixin Zheng; Alejandro A. Schäffer; Janet K. Dale; Joie Davis; Roxanne E. Fischer; Stephen E. Straus; Donna Boruchov; Frank T. Saulsbury; Michael J. Lenardo; et al. (Human Genetics, 2006)

An analysis of genetic variation across the MBL2 locus in Dutch Caucasians indicates that 3′ haplotypes could modify circulating levels of mannose-binding lectin - Toralf Bernig; Willemijn Breunis; Nannette Brouwer; Amy Hutchinson; Robert Welch; Dirk Roos; Taco Kuijpers; Stephen Chanock (Human Genetics, 2005)

Time course of the effects of the serotonin-selective reuptake inhibitor sertraline on central and peripheral serotonin neurochemistry in the rhesus monkey - George M. Anderson; Christina S. Barr; Stephen Lindell; Amy C. Durham; Ilya Shifrovich; J. Dee Higley (Psychopharmacology, 2005)

Transgenic Mice Over-expressing Endothelin-1 in Testis Transactivated by a Cre/loxP System Showed Decreased Testicular Capillary Blood Flow - Amy C.Y. Lo; Maggie K.L. Fung; C.L. Au; Theobald S.K. Chan; Brian Sauer; Stephen S.M. Chung; Sookja K. Chung (Transgenic Research, 2004)

Erosion and the Rejuvenation of Weathering-derived Nutrient Supply in an Old Tropical Landscape - Peter Vitousek; Oliver Chadwick; Pamela Matson; Steven Allison; Louis Derry; Lisa Kettley; Amy Luers; Esther Mecking; Valerie Monastra; Stephen Porder (Ecosystems, 2003)

The discriminative stimulus properties of self-administered ethanol are mediated by GABA A and NMDA receptors in rats - Clyde W. Hodge; Amy A. Cox; Alison M. Bratt; Rosana Camarini; Kimberly Iller; Stephen P. Kelley; Kristin K. Mehmert; Michelle A. Nannini; M. Foster Olive (Psychopharmacology, 2001)

Structure and expression of duplicate AGAMOUS orthologues in poplar - Amy M. Brunner; William H. Rottmann; Lorraine A. Sheppard; Konstantin Krutovskii; Stephen P. DiFazio; Stefano Leonardi; Steven H. Strauss (Plant Molecular Biology, 2000)

Why Economics Matters for Endangered Species Protection - Jason F. Shogren; John Tschirhart; Terry Anderson; Amy Whritenour Ando; Steven R. Beissinger; David Brookshire; Gardner M. Brown; Don Coursey; Robert Innes; Stephen M. Meyer; Stephan Polasky (Conservation Biology, 1999)
We offer three reasons why economics matters more to species protection than many people think and what this implies for the ongoing debate over the reauthorization of the Endangered Species Act of 1973. Economics matters because (1) human behavior generally, and economic parameters in particular, help determine the degree of risk to a species; (2) in a world of scarce resources, the opportunity cost of species protection—the costs of reduced resources for other worthwhile causes—must be taken into account in decision making; and (3) economic incentives are critical in shaping human behavior, and consequently the recovery of species. Endangered species protection that explicitly addresses these basic principles can avoid wasting valuable resources that yield no gain in species protection.